Formulasi Dan Uji Antibakteri Porphyromonas Gingivalis Sediaan Gargarisma Ekstrak Daun Pacar Air (Impatiens Balsamina L.): Formulation And Antibacterial Test Porphyromonas Gingivalis Of Gargarisma Extract Water Henna Leaves (Impatiens Balsamina L. - Yuniarto, Prayoga Fery; Sukmawati, Datin An Nisa; Lambert, Maringan; Witaning, Leny; hidayah, lailatul; Virginia, Vivi (Jurnal Inovasi Farmasi Indonesia (JAFI), 2025)
Porphyromonas gingivalis is one of the anaerobic gram-negative bacteria that causes dental and oral health problems that will cause periodontal disease, especially chronic periodontitis. Water henna leaf (Impatiens balsamina L) is one of the plants can be used as an antibacterial drug. This study aims to determine the antibacterial activity of the formulation of Gargarisma leaf extract of henna water against Porphyromonas gingivalis bacteria. The method used in the antibacterial activity test is the diffusion method. The ethanol extract of henna leaf ethanol extract was tested, namely organoleptic test, homogeneity test, pH test and viscosity test. Then proceed with data analysis with One Way ANOVA. This study used 3 formulas with different extract concentrations of 10%, 15%, and 20%, positive control (Chlorhexidine Gluconate), and negative control (aquades). The results of the antibacterial activity test of gargarisma preparations obtained that the average inhibition zone at 10% concentration was 10.97 mm, 15% concentration was 12.02 mm, 20% concentration was 13.76 mm, positive control was 17.9 mm, and aquadest negative control did not show any antibacterial activity.